**Quadratic Equations**

A quadratic equation has the form $ax^2 + bx + c=0$, where $a, b$, and $c$ are real numbers, and $a \neq 0$. The $ax^2$ term is called the quadratic term, the $bx$ is the linear term, and $c$ is called the constant term. Consider the quadratic equation $x^2 – x -6=0$, if we substitute $x=3$ in this equation we find that the equation holds true because $3^2-3-6=9-9=0$. Similarly if we substitute $x=-2$ in this equation we again find that $ (-2)^2 – (-2) – 6 = 4+2-6=0$. These two values of $x$ are the only two numbers that satisfy this quadratic equation, and are called the roots of the quadratic equation. Sometimes the roots are also referred to as zeros of the quadratic equation, in other words the value of the quadratic expression is zero at these values.

**Factoring Quadratics: Trial and Error**

The roots of the quadratic equation $x^2 – x -6=0$ can be obtained by factoring the equation into a product of binomials. Let’s assume that the binomials are $x+r_1$ and $x+r_2$, our goal is to find the values of $r_1$ and $r_2$ such that: $$(x+r_1)(x+r_2) = x^2 – x -6$$ $$x^2 + (r_1+r_2)x + r_1r_2 = x^2 – x -6$$ The two expressions above are identical and therefore the coefficient of $x$ terms must be equal or $r_1+r_2=-1$. Similarly, the constant terms must also be equal, therefore $r_1 r_2=-6$. By using trial and error we find that the values of $r_1$ and $r_2$ are $2$ and $-3$. Therefore our quadratic equation can be rewritten as $$x^2 – x -6 = (x+2)(x-3) =0$$ For the above equation to hold true, either $x+2=0$ or $x-3=0$, which tells us that $x=-2$ and $x=3$ are the solutions to this quadratic equation.

**Factoring Quadratics: General Case**

When the coefficient of the $x^2$ term is not 1 we follow the steps described below to factor the quadratic equation. I will use the example of $2x^2-5x-33=0$.

- Multiply the coefficient of $x^2$, $2$ in this case, and the constant term of $-33$, which gives a value of $-66$.
- Use trial and error to find two numbers that multiply to give $-66$ but add up to the coefficient of $x$, which is $-5$.
- The two numbers are $-11$ and $6$.
- Rewrite the middle term as the sum of these two numbers $-5x = -11x+6x$.

$$ 2x^2-5x-33=2x^2-11x + 6x-33=0 $$ Factor the largest common term from the first two terms, and also from the last two terms. $$ x(2x-11) + 3(2x-11)=0$$ $$(2x-11)(x + 3)=0 \quad \text{Factor $(2x-11)$} $$ - The roots are then obtained by solving $2x-11=0$ and $x+3=0$, which gives $\dfrac{11}{2}$ and $-3$ as the

two roots of the quadratic equation $2x^2-5x-33=0$.

**Completing a Square**

Completing a square refers to the process of adding a constant term to a quadratic expression such that the result is a perfect square. Consider the expression $x^2+6x+4$, we can rewrite this as $$x^2+6x+9-9+4=x^2+6x+9-5$$ We further recognize that $x^2+6x+9=(x+3)^2$ is a perfect square, and therefore the original expression is equivalent to $(x+3)^2-5$.

In general if we are given a quadratic of the form $x^2+bx$, we add $\left(\dfrac{b}{2}\right)^2$ to the quadratic to obtain a perfect square. $$ x^2 + bx + \left(\dfrac{b}{2}\right)^2 = x^2+ bx + \dfrac{b^2}{4} = \left(x+ \dfrac{b}{2}\right)^2$$

**Quadratic Expressions: Maximum and Minimum**

Completing the square of a quadratic expression helps us to find the least and greatest value of such expressions. In general the quadratic expression $ax^2+bx+c$ attains its maxima ($a<0$) or minima ($a>0$) when $x = -\dfrac{b}{2a}$. The greatest and the least value of the quadratic expression can be found by substituting $x=-\dfrac{b}{2a}$ into the expression $ax^2+bx+c$.

**Solved Example:** $$ h(t) = -16t^2+24t+18$$

The equation above gives the height above ground $h$, in feet, of a ball $t$ seconds after it is launched vertically upward from a platform that is at a height of 18 feet. What is the greatest height the ball achieves?

- $21$
- $24$
- $27$
- $30$

**Explanation:**The easiest way to solve this problem is by recognizing that the maximum value of the expression occurs when $t = -\dfrac{b}{2a}= -\dfrac{24}{2(-16)} = \dfrac{3}{4}$, and we can find the maximum height by substituting $t=\dfrac{3}{4}$ in the expression $-16t^2+24t+18= -16\left(\dfrac{3}{4}\right)^2 + 24\left(\dfrac{3}{4}\right) + 18 = -9 + 18 + 18 = 27$.

We can also do this problem by completing the square, we first factor out the term $-16$ from the first two terms of the quadratic expression to obtain:

$$

\begin{align}

h(t) &= -16t^2+24t+18 && \text{Factor out $-16$}\\

&= -16\left[t^2 – \dfrac{3}{2}\right] + 18 && \text{Complete the square} \\

&=-16\left[t^2 – \dfrac{3}{2}+ \left(\dfrac{3}{4}\right)^2 – \left(\dfrac{3}{4}\right)^2\right] + 18 && \text{} \\

&= -16\left[t^2 – \dfrac{3}{2}+ \left(\dfrac{3}{4}\right)^2\right] +16\left(\dfrac{3}{4}\right)^2+ 18 && \text{}\\

& = -16\left(t-\dfrac{3}{4}\right)^2 + 27 && \\

\end{align}

$$

Note that the expression $\left(t-\dfrac{3}{4}\right)^2 \geq 0$ because it is a square of a number. This means that the term $-16\left(t-\dfrac{3}{4}\right)^2$ will always be less than or equal to zero. The maximum height will have a value of $27$ and this will happen when $t=\dfrac{3}{4}$.

**Quadratic Formula**

The quadratic formula can be used to obtain the solutions to the general quadratic equation $ax^2 + bx + c=0$:

$$ x = \dfrac{-b \pm \sqrt{b^2-4ac}}{2a} $$

**Example**: $2x^2-5x-33=0$, we have $a=2$, $b=-5$, and $c=-33$, replacing these values in the above quadratic formula yields $$ x = \dfrac{-(-5) \pm \sqrt{(-5)^2-4(2)(-33)}}{2(2)}=\dfrac{5 \pm \sqrt{289}}{4} = \dfrac{5 \pm 17}{4}$$ and the two solutions are $x=\dfrac{11}{2}$ and $x=-3$.

**Solved Example:** $$ \dfrac{x^2}{2} = mx + \dfrac{n}{2} $$

In the quadratic equation above, $m$ and $n$ are constants. What are the solutions for $x$ ?

- $\quad m \pm \sqrt{m^2-n}$
- $\quad m \pm \sqrt{m^2+n}$
- $\quad -m \pm \sqrt{m^2-n}$
- $\quad -m \pm \sqrt{m^2+n}$

**Explanation:** $$

\begin{align}

\dfrac{x^2}{2} &= mx + \dfrac{n}{2} && \text{Multiply both sides by 2}\\

x^2 &= 2mx +n && \text{Rewrite in standard form} \\

x^2 – 2mx – n &=0 && \text{Note $a=1$, $b=-2m$, $c=-n$} \\

x &= \dfrac{-b \pm \sqrt{b^2-4ac}}{2a} && \text{Apply quadratic formula}\\

& = \dfrac{-(-2m) \pm \sqrt{(-2m)^2-4(1)(-n)}}{2(1)} && \\

& = \dfrac{2m \pm \sqrt{4m^2+4n}}{2} &&\\

& = \dfrac{2m \pm 2\sqrt{m^2+n}}{2} && \text{Divide throughout by 2}\\

& = m \pm \sqrt{m^2+n} &&\\

\end{align}

$$

**Sum and Product of Roots**

Let $r_1$ and $r_2$ be the roots of the quadratic equation $ax^2 + bx + c=0$, then the quadratic equation in the factored form can be written as $a(x-r_1)(x-r_2)=0$. If we multiply this expression and rearrange it, we obtain:

$$

\begin{align}

a(x-r_1)(x-r_2)&=0 &&\\

a(x^2 – xr_2 – xr_1 + r_1 r_2) &=0 &&\\

a[x^2 -x(r_1+r_2)+r_1r_2] &=0 &&\\

ax^2-xa(r_1+r_2)+ar_1r_2 &=0 &&\\

\end{align}

$$

This resulting expanded form is equivalent to the quadratic equation $ax^2 + bx + c=0$, and the coefficient of all the terms must be identical. If we equate the coefficient of $x$ term we obtain $-a(r_1+r_2) = b$, or in other words:

$$\textrm{Sum of Roots} = r_1 + r_2 = -\dfrac{b}{a} $$ Further if we equate the constant part of the two equations, we obtain $ar_1r_2=c$, or in other words: $$ \textrm{Product of Roots} = r_1 r_2 = \frac{c}{a} $$ The above two formulas are helpful in finding the sum and product of the roots without having to find the roots themselves.

**Solved Example:** $$ 2x^2=3x+2 $$ What is the sum of all the solutions to the quadratic equation above?

- $\quad -\dfrac{5}{2}$
- $\quad -\dfrac{3}{2}$
- $\quad \quad \dfrac{3}{2}$
- $\quad \quad \dfrac{5}{2}$

**Explanation:** Rewrite the equation in the standard quadratic form $ax^2+bx+c=0$ as $2x^2-3x-2=0$. We have $a=2$, $b=-3$, and $c=-2$. The sum of the roots is equal to $-\dfrac{b}{a}=-\dfrac{(-3)}{2} = \dfrac{3}{2}$. There is no need to waste time in first finding the two roots, which are $-\dfrac{1}{2}$ and $2$, and adding them to find their sum of $\dfrac{3}{2}$.

**Nature of Roots**

The table below summarizes how the discriminant $b^2-4ac$ determines the nature of the roots of a general quadratic equation $ax^2+bx+c=0$, and where the corresponding graph of the parabola $y=ax^2+bx+c=0$ falls with respect to the $x-$axis. I will review parabolas in a different article.

$$

\begin{array}{|c|c|c|}

\hline

\textbf{Condition} & \textbf{Nature of Roots} & \textbf{Graph of the}\\

& & \textbf{corresponding parabola} \\ \hline

b^2 – 4ac > 0 & \text{Roots are distinct and real} & \text{Parabola intersects the $x-$axis}\\

& & \text{at two distinct points}\\ \hline

b^2 – 4ac < 0 & \text{No real roots} & \text{Parabola does not }\\
& & \text{intersect the $x-$axis}\\ \hline
b^2 - 4ac = 0 & \text{Roots are identical} & \text{Parabola is tangent} \\
& \text{also called a double root} & \text{to the $x-$axis}\\ \hline
\end{array}
$$
**Example:** If $b$ is a constant such that the equation $2x^2=bx-3$ has two distinct real solutions, which of the following could be the value of $b$ ?

- $\quad -5$
- $\quad -4$
- $\quad -3$
- $\quad 4$

**Explanation:** First write the quadratic equation in the standard form $2x^2-bx+3=0$. For the roots to be real and distinct $b^2-4ac>0$, which is equivalent to $(-b)^2 – 4(2)(3)>0$ or $b^2>24$. The only value in the answer choices that satisfies this condition is $-5$.

Hernan says

Really great summary. Thank you for it!!!

Er manohar lal Yadav says

Sir , Wonderful and step by step solution makes it easy for student to learn very easily .

jacko lac says

Thank you that was useful same as the course i was in

Justin says

Your veta theorem example did not have a correct answer.

Dabral says

Thank you for pointing out the error.

I am assuming you are referring to this question:

$$2x^2=3x+2$$

What is the sum of all the solutions to the quadratic equation above?

I had mistyped one of the answer choices.